Anaesthetic effects of different concentrations of sodium bicarbonate on common carp (Cyprinus carpio) - Leah Joyce B. Gajutos; Aurelia B. Gajutos (Journal of Fisheries, 2023)
Sedation of fish before handling and transporting can help curtail undue stress that can affect their health.  This study investigated the effectiveness of sodium bicarbonate (NaHCO3) utilised as an anaesthetic agent for common carp (Cyprinus carpio) with an average weight of 13.5 ± 0.55 g. The experimental fish were grouped and exposed to different concentrations at 0, 40, 45 and 50 g L–1 of NaHCO3 dissolved in water. Fishes were bath-immersed in different concentrations of NaHCO3 solution until such time that they became anesthetised. Results showed that induction time and recovery time increases with increasing NaHCO3 concentration. All fish reached complete anaesthesia in more than 3 minutes under a higher concentration of 50 g L–1. No mortality occurred under any of the concentrations tested. The most optimal concentration leading to complete anaesthesia in 2 minutes and recovery in less than 4 minutes was 45 g L–1.  This study showed that NaHCO3 is a potential fish anaesthetic for the common carp.